Formulação de políticas públicas de segurança no Brasil e a primeira conferência nacional de segurança pública - Vilela, Fábio Alves de Castro (2018)
This research studied government actions, processes, tactics, strategies or programs with the potential to substantiate any type of security policy formulated in accordance with the principles and guidelines deliberate at the first national conference of public safety in Brazil. In this way, using a hypothetical deductive thinking approach, by means of the hypothesis that more than half of the normative acts formulated by the Brazilian Congress, after the publication of this conference report’s, governmental actions, processes, tactics, strategies, or programs with the potential to substantiate some kind of security policy have been related to the principles and guidelines it has deliberately, tried demonstrate, comparatively, the percentage found between the principles and the guidelines and what has been produced by the public power in this sector. The work begins with a bibliographical research on policy and theories about participatory and deliberate democracy, to analyze the final report of the first national conference of public safety in Brazil, concerned to the data related to the government acts in question, arranged in the network information systems (INTERNET) of the Brazilian Congress and the Justice Ministry, extracting the necessary information to assist in the filling of gaps of scientific knowledge that Can explain the formulation and security policy design’s in Brazil. As result, the hypothesis was confirmed, demonstrating the percentage achieved by these acts, including in relation to each principle and guideline.